1910
DOI: 10.1037/h0093038
|View full text |Cite
|
Sign up to set email alerts
|

Some mental processes of the rhesus monkey.

Abstract: with the cooperation of Mans Distinguished Psychologists THE PSYCHOLOGICAL REVIEW containing ordinal contributions only, appears bimonthly , or. the first of January. March, May, July, September, and November, the six numbers comprising a volume of about 4:0 pages. THE PSYCHOLOGICAL BULLETIN containing"critical reviews, notices of book? and articles, psychological news and notes, university notices, announcements, , Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1911
1911
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…However, there are both anecdotal (Cook, Brower, & Alcock, 1969;Gans, 1964;Rothschild & Ford, 1967;Swynnerton, 1942;von Steiniger, 1950) and laboratory (Friese & Lavin, 1978;Jouventin, Pasteur, & Cambefort, 1977;Klopfer, 1957) obser-vations to support the notion that both mammals and birds can learn to avoid unpalatable (and often fatal) food items through their interaction with conspecifics and can overcome previously formed aversions through social learning (Alcock, 1969;Turner, 1964). Because social learning seems to play an important role in the transmission of food-related behaviors, the question arises why so many attempts to demonstrate social learning in the laboratory have been unsuccessful (Brogden, 1942;Bruce, 1941;Cole, 1907;Davis, 1903;Klopfer, 1959Klopfer, , 1961Powell, 1968;Powell, Saundere, & Thompson, 1968;Sexton & Finch, 1967;Sheperd, 1910Sheperd, , 1911Sheperd, , 1923Small, 1900;Thorndike, 1898;Watson, 1908;Yerkes, 1927) or at best equivocal (Alcock, 1969;Bayroff & Lard, 1944;Corson, 1967;Dawson & Foss, 1965;Hayes & Hayes, 1952;Oldfield-Box, 1970;Small, 1900).…”
Section: Discussionmentioning
confidence: 98%
“…However, there are both anecdotal (Cook, Brower, & Alcock, 1969;Gans, 1964;Rothschild & Ford, 1967;Swynnerton, 1942;von Steiniger, 1950) and laboratory (Friese & Lavin, 1978;Jouventin, Pasteur, & Cambefort, 1977;Klopfer, 1957) obser-vations to support the notion that both mammals and birds can learn to avoid unpalatable (and often fatal) food items through their interaction with conspecifics and can overcome previously formed aversions through social learning (Alcock, 1969;Turner, 1964). Because social learning seems to play an important role in the transmission of food-related behaviors, the question arises why so many attempts to demonstrate social learning in the laboratory have been unsuccessful (Brogden, 1942;Bruce, 1941;Cole, 1907;Davis, 1903;Klopfer, 1959Klopfer, , 1961Powell, 1968;Powell, Saundere, & Thompson, 1968;Sexton & Finch, 1967;Sheperd, 1910Sheperd, , 1911Sheperd, , 1923Small, 1900;Thorndike, 1898;Watson, 1908;Yerkes, 1927) or at best equivocal (Alcock, 1969;Bayroff & Lard, 1944;Corson, 1967;Dawson & Foss, 1965;Hayes & Hayes, 1952;Oldfield-Box, 1970;Small, 1900).…”
Section: Discussionmentioning
confidence: 98%
“…It was found that the animal "showed a prompt narrowing down of the field of effort to the right feature of the situation" (namely the door button); but that "this important factor in the process of learning seemed to be accompanied by a complete absence of insight into the mechanical principle involved." Shepherd (14,15) interpreted the behavior of his rhesus monkeys and chimpanzees, and Kinnamanx (8) the behavior of his rhesus monkeys in terms of the trial-and-error theory.…”
Section: Background Op the Problemmentioning
confidence: 99%
“…In a series of experiments on the color discrimination of monkeys, conducted by Dr. W. T. Shepherd (68), under my direction it was found that the animal rapidly learned to discriminate colored objects if the stimuli were of a character to attract and to hold the attention. In most animal experimentation it has been found difficult to get stimuli which will attract the attention of the animal, stimuli which are appreciated by the animal and which will lead to definite reactions.…”
Section: Shepherd Ivory Franzmentioning
confidence: 99%